2017
DOI: 10.1063/1.4973979
|View full text |Cite
|
Sign up to set email alerts
|

Local spin dynamics of iron oxide magnetic nanoparticles dispersed in different solvents with variable size and shape: A 1H NMR study

Abstract: Colloidal magnetic nanoparticles (MNPs) based on a nearly monodisperse iron oxide core and capped by oleic acid have been used as model systems for investigating the superparamagnetic spin dynamics by means of magnetometry measurements and nuclear magnetic resonance (H NMR) relaxometry. The key magnetic properties (saturation magnetization, coercive field, and frequency dependent "blocking" temperature) of MNPs with different core size (3.5 nm, 8.5 nm, and 17.5 nm), shape (spherical and cubic), and dispersant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 35 publications
(44 reference statements)
1
38
0
Order By: Relevance
“…3B, solid lines). A similar mismatch has previously been observed 26,27 and attributed to one or more physical mechanisms not included in the model itself. On this respect, it should be observed that the RMG model describes systems in the so called motional averaging regime (in short MAR, corresponding to fast motions) while our systems are out of the limit of the MAR regime.…”
Section: H Nmr Relaxometric Characterizationsupporting
confidence: 81%
“…3B, solid lines). A similar mismatch has previously been observed 26,27 and attributed to one or more physical mechanisms not included in the model itself. On this respect, it should be observed that the RMG model describes systems in the so called motional averaging regime (in short MAR, corresponding to fast motions) while our systems are out of the limit of the MAR regime.…”
Section: H Nmr Relaxometric Characterizationsupporting
confidence: 81%
“…When comparing samples containing cubic shaped IOMNPS (samples 1-3 in Figure 6a), theoretically, maximum signal intensity should be observed for sample 1 as Tevol ≈ T1. In practice, the dreMR contrast in Figure 8 is altered by an additional T2-weighting due to short T2 of the IOMNPs [19]. Consequently, the samples with the highest concentrations seemingly paradoxically, show less contrast enhancement, though, in reality, their T1 enhancement is maximal.…”
Section: Dremr Signal Simulationmentioning
confidence: 96%
“…In order to validate the implementation of the FFC-MRI hardware setup, the availability of a contrast agent exhibiting strong R1 relaxation dispersion at 3 T is crucial. Recently published iron oxide magnetic nanoparticles [19] were selected for system validation because of a suspected R1 dispersion at 3 T. Such IOMNPs are obtained by a high temperature surfactantassisted chemical route which leads to size-and shape-controlled nanocrystals. IOMNPs with similar average size (nearly 8 nm) and with different shapes (spherical and cubical) were used dispersed in hexane, and will be referred to as S8_hex and C8_hex, respectively.…”
Section: Dispersive Contrast Agent For 3 T and Ffc Measurementsmentioning
confidence: 99%
“…Unfortunately, those equations do not seem able to match the experimental results for transverse relaxation. Indeed, recent studies have shown that it was not possible to fit longitudinal and transverse NMRDs at the same time—indicating that a relaxation mechanism may miss in the models, at least for the transverse relaxation rate . Moreover, most of the experimental R 2 ‐NMRDs seem to exhibit a monotonously increase of R 2 with B 0 while the theoretical predictions predict a decrease of R 2 before it reaches a plateau.…”
Section: Nuclear Magnetic Relaxation Induced By Superparamagnetic Parmentioning
confidence: 98%
“…While theoretical predictions are available, significant variations of the transverse relaxation are expected to occur at fields so low that it is technically very difficult to measure the signal decay. In the dominant Néel relaxation model, this is given by R 2 * = 1 T 2 * = 16 π 135 μ 0 4 π 2 μ normalS normalP normalM 2 γ p 2 C R normalS normalP normalM D R ' Neel (),,,,, P ω S ω p τ D τ N x R ' Neel (),,,,, P ω S ω I τ D τ N x = L () x x () 13 P J F (),, ω S τ D τ N + 7 () 1 P J F (),, ω I τ D τ N + 6 () 1 P J F (),, 0 τ D τ N + () 1 2 L () x x L 2 () x () 3 J F (),, ω I τ D τ N + 4 J F (),, 0 τ D τ N + L 2 () x () 3 J A (), ω I τ D + 4 J A (), 0 τ D . …”
Section: Nuclear Magnetic Relaxation Induced By Superparamagnetic Parmentioning
confidence: 99%